2018
DOI: 10.12659/msm.912808
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minimally Invasive and Open Transforaminal Lumbar Interbody Fusion for Lumbar Disc Herniation: A Retrospective Cohort Study

Abstract: BackgroundThis cohort study compared the efficacy and safety of minimally invasive versus open transforaminal lumbar interbody fusion (Mis-TLIF versus Open-TLIF) for lumbar disc herniation with radiculopathy.Material/MethodsFrom July 2016 to September 2017, we recruited 37 patients suffering from lumbar disc herniation with radiculopathy. Seventeen patients underwent Mis-TLIF (Mis group) and 20 patients underwent Open-TLIF (Open group). Baseline characteristics were similar between the 2 groups before surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…A multitude of studies have shown a certain superiority of MIS for PLIF and TLIF approaches. 5,14,15,31 Perioperative outcomes like blood loss, 5,14,15 length of stay, 5,14,31 and operative time have shown to be improved in patients undergoing MIS compared to open procedures. 5 Additionally in…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of studies have shown a certain superiority of MIS for PLIF and TLIF approaches. 5,14,15,31 Perioperative outcomes like blood loss, 5,14,15 length of stay, 5,14,31 and operative time have shown to be improved in patients undergoing MIS compared to open procedures. 5 Additionally in…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been developed to control bleeding during spinal surgery and mainly include minimal invasion procedures, patient positioning, deliberate hypotension, intraabdominal pressure control, infiltration of paraspinal tissues using vasoconstrictors, and pharmacological agents to enhance coagulation [10,[22][23][24][25]. TXA is known as an antifibrinolytic agent and acts through blocking the interaction of plasminogen and plasmin by competing with the lysine residues on the surface of fibrin to inhibit the fibrinolysis, resulting in clot stabilization [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Transforaminal lumbar interbody fusion (TLIF) has been widely accepted to treat these diseases and is associated with less trauma and blood loss compared to posterior lumbar interbody fusion [4][5][6]. However, extensive paravertebral muscle stripping and retraction is still needed to obtain an adequate surgical field during TLIF [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Successful surgery requires a motionless and clear surgical field, and even minimal bleeding interfering with the visualization of the operative area can lead to increased operative time and complications. [2830] Previous study reports that magnesium sulfate is capable of reducing arterial pressure, heart rate, blood loss, and duration of sinus surgery. [15] Improved quality of the surgical field is observed after magnesium sulfate application during endoscopic sinus surgery.…”
Section: Discussionmentioning
confidence: 99%